Structure and Processes of Existing Practice in Radiotherapy Peer Review: A Systematic Review of the Literature. Issue 4 (April 2021) - Lewis, P.J.; Court, L.E.; Lievens, Y.; Aggarwal, A.
Abstract: Peer review in radiotherapy is an essential step in clinical quality assurance to avoid planning-related errors that can impact on patient safety and treatment outcomes. Despite recommendations that radiotherapy centres should include peer review in their regular quality assurance pathway, adoption of the practice has not been universal, and to date there have been no formal guidelines set out to standardise the process. We undertook a systematic review of the literature to determine existing practice in radiotherapy peer review internationally, with respect to meeting structure and processes, in order to define a standardised framework. A PubMed and Web of Science search identified 17 articles detailing peer review practice. The results revealed significant variation in peer review processes between institutions, and a lack of consensus on documentation and reporting. Variations in the grading of outcomes of peer review were also noted. Taking into account the results of this review, a framework for standardising the process and outcome documentation for peer review has been developed. This can be utilised by radiotherapy centres introducing or updating peer review practice, and can facilitate meaningful evaluation of the clinical impact of peer review in the future. Highlights: Peer review is essential to ensure safe and effective radiotherapy treatment. Despite recommendations, there are no formal guidelines for the peer review process. This systematic review highlights variation in peer review practice internationally. We propose a framework for peer review processes and outcome documentation. This standardised approach can facilitate meaningful analysis of peer review impact.